Implementasi Pengelolaan Penghidupan Keluarga Sakinah - Beddu, Muhammad Juni; Mas'ari, Ahmad; Yanti, Novi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study addresses the economic and financial challenges faced by families in Pekanbaru, a major economic and social hub on the island of Sumatra, where many families have low incomes and rely on zakat and infaq assistance to meet their basic needs. High urbanization rates also influence the way families manage their lives. The objective of this research is to identify and analyze the issues families in Pekanbaru face in managing their livelihoods, using a descriptive qualitative approach to comprehensively collect and depict data. The data is analyzed through content analysis to gain a deeper understanding of the challenges. The concept of "sakinah family" used in this study refers to families built on lawful marriages, capable of fulfilling both spiritual and material needs in a balanced manner, and prioritizing values of affection within the family and social environment. The implementation of this concept in Pekanbaru involves financial management, participation in productive activities, and engagement in social and political activities. Findings indicate that families managing their incomes under the principles of sakinah have more prudent financial planning and joint financial decision-making between spouses. This sakinah family management approach shows potential for enhancing the welfare and harmony of families in Pekanbaru through balanced financial practices aligned with Islamic teachings.